The Determination of the Homogeneity of a Vitis vinif era L. cv. Cape Riesling Vineyard - De La Harpe, A. C.; Visser, J. H. (South African Journal of Enology and Viticulture, 2017)
The value of Principal Component and Stepwise Discriminant analyses in selecting uniform plants for experimental purposes is discussed. Twenty seven variables were taken into account to establish the homogeniety (uniform plants) of 297 Vitis vinifera L. cv. Cape Riesling vines. A detailed study of the relationship and interrelationship of these variables resulted in 208 vines being selected as a uniform population. This selection provides the researcher with the possibility of using single vines as experimental units. However, it must be pointed out that Principal Component and Stepwise Discriminant analyses can only be used as an aid to normal statistical evaluation of experimental results and not as substitute for statistical experimental design.